Anticancer Compounds Derived from Marine Diatoms - Hussein, Hanaa Ali (Mar Drugs, 2020)
Cancer is the main cause of death worldwide, so the discovery of new and effective therapeutic agents must be urgently addressed. Diatoms are rich in minerals and secondary metabolites such as saturated and unsaturated fatty acids, esters, acyl lipids, sterols, proteins, and flavonoids. These bioactive compounds have been reported as potent anti-cancer, anti-oxidant and anti-bacterial agents. Diatoms are unicellular photosynthetic organisms, which are important in the biogeochemical circulation of silica, nitrogen, and carbon, attributable to their short growth-cycle and high yield. The biosilica of diatoms is potentially effective as a carrier for targeted drug delivery in cancer therapy due to its high surface area, nano-porosity, bio-compatibility, and bio-degradability. In vivo studies have shown no significant symptoms of tissue damage in animal models, suggesting the suitability of a diatoms-based system as a safe nanocarrier in nano-medicine applications. This review presents an overview of diatoms’ microalgae possessing anti-cancer activities and the potential role of the diatoms and biosilica in the delivery of anticancer drugs. Diatoms-based antibodies and vitamin B12 as drug carriers are also elaborated.